Empreendedorismo e estratégia: estudo de múltiplos casos de criação de empresas no setor de refrigerantes no Ceará - Donato, José Varela (2011)
This research aims to describe how the process of creating two companies and their competitive strategies have developed in the carbonated soft drinks sector in the State of Ceará. It is a qualitative and descriptive research, in which interpretation plays a crucial role in data analysis, that consisted mainly of texts originated from interviews with the founders and general managers of two companies studied and managers of three supermarket chains as well as documents, articles, studies and statistics from the carbonated soft drinks sector. The research revealed that the entrepreneurial processes occured in a disordely way, the discovery of an opportunity resulted of a set of conditions, the entrepreneurs did not compare opportunities and used rational and non-rational criteria for evaluating opportunities, they didn’t have a long-term goal or vision at the beginning of their companies and exhibited confidence and optimism about the success of their business. Regarding the creation of competitive strategy, the results show that competition occurred in all segments of the value chain of companies, a cost leadership strategy was effective for entry into the market, but an obstacle to growth in face of changes in the economic profile and lifestyle of consumers; the intangible assets (brand reputation, knowledge, education for entrepreneurship, for example) and capabilities to effectively perform the activities in the value chain are more sustainable and valuable competitive advantages to business performance. Finally, the research results suggest that the development and evaluation of business creation projects must incorporate variables such as increasing the number of firms and their survival and mortality rates, entry costs, capacity utilization, and competitive movements in broader geographic areas.